2003
DOI: 10.1128/aem.69.5.2674-2683.2003
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Genetic Lesions of the Arginine and Pyrimidine Biosynthetic Pathways in Lactobacillus plantarum , L. paraplantarum, L. pentosus , and L. casei : Prevalence of CO 2 -Dependent Auxotrophs and Characterization of Deficient arg Genes in L. plantarum

Abstract: Lactic acid bacteria require rich media since, due to mutations in their biosynthetic genes, they are unable to synthesize numerous amino acids and nucleobases. Arginine biosynthesis and pyrimidine biosynthesis have a common intermediate, carbamoyl phosphate (CP), whose synthesis requires CO 2 . We investigated the extent of genetic lesions in both the arginine biosynthesis and pyrimidine biosynthesis pathways in a collection of lactobacilli, including 150 strains of Lactobacillus plantarum, 32 strains of L. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 36 publications
(36 reference statements)
1
46
0
Order By: Relevance
“…The effect of inorganic carbon concentrations on two L. plantarum strains was tested. Strain NCIMB 8826, the L. plantarum whose genome has been sequenced, requires CO 2 -enriched air to grow on defined media plates when arginine and pyrimidines are absent [4]. The other strain, CCM 1904 (equivalent to ATCC 8014), is prototrophic for arginine and pyrimidines and grew in normal air.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of inorganic carbon concentrations on two L. plantarum strains was tested. Strain NCIMB 8826, the L. plantarum whose genome has been sequenced, requires CO 2 -enriched air to grow on defined media plates when arginine and pyrimidines are absent [4]. The other strain, CCM 1904 (equivalent to ATCC 8014), is prototrophic for arginine and pyrimidines and grew in normal air.…”
Section: Resultsmentioning
confidence: 99%
“…High-CO 2 -requiring natural auxotrophs are prevalent in natural isolates of L. plantarum without arginine and pyrimidine supplements [4]. This suggests that inorganic carbon is required as a substrate of CPS.…”
Section: How Does Inorganic Carbon Stimulate L Plantarum Growth?mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies (Bringel & Hubert, 2003 have suggested that LAB evolve by progressively losing unnecessary genes upon adaptation to some specific habitats. DNA degeneration by spontaneous mutation may inactivate unnecessary genes during their adaptation to specific habitats in order to improve the growth or cell viability under the stressful or unusual conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Once LAB have adapted to some rich environments, they may lose the ability to synthesize many essential amino acids and vitamins. Most of these genetic lesions have been found to be located in genes rather than in the promoter regions (Delorme et al, 1993;Godon et al, 1993;Cavin et al, 1999;Nomura et al, 2000;Bringel & Hubert, 2003. A systematic attempt to isolate mutants that no longer require each of the essential amino acids has been undertaken for several lactobacilli (Morishita et al, 1974(Morishita et al, , 1981Bringel & Hubert, 2003, including Enterococcus, Pediococcus and Lactococcus species (Deguchi & Morishita, 1992).…”
Section: Discussionmentioning
confidence: 99%